2017
DOI: 10.1101/171397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OptoGap: an optogenetics-enabled assay for quantification of cell-cell coupling in multicellular cardiac tissue

Abstract: Intercellular electrical coupling is an essential means of communication between cells. It is important to obtain quantitative knowledge of such coupling between cardiomyocytes and nonexcitable cells when, for example, pathological electrical coupling between myofibroblasts and cardiomyocytes yields increased arrhythmia risk or during the integration of donor (e.g. cardiac progenitor) cells with native cardiomyocytes in cell-therapy approaches. Currently, there is no direct method for assessing heterocellular … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…al [16] that addition of MFBs to CM cultures causes RP elevation, conduction slowing, and spontaneous beating, a number of studies have attributed MFB-induced conduction slowing to electrical coupling between CMs and MFBs [14][15][16][17][18]36]. Some studies used FRAP as evidence of diffusional (and therefore presumably electrical) coupling between CMs and MFBs [17], but these cannot be translated to a value of electrical conductance [37] or show that the connection is strong enough to cause significant slowing. Dual-cell patch clamp has been used to quantify the electrical connection between CM and MFB pairs [14,38], but not in a syncytium, which allows for measurement of macroscopic CV, and has different electrophysiology than single cells [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al [16] that addition of MFBs to CM cultures causes RP elevation, conduction slowing, and spontaneous beating, a number of studies have attributed MFB-induced conduction slowing to electrical coupling between CMs and MFBs [14][15][16][17][18]36]. Some studies used FRAP as evidence of diffusional (and therefore presumably electrical) coupling between CMs and MFBs [17], but these cannot be translated to a value of electrical conductance [37] or show that the connection is strong enough to cause significant slowing. Dual-cell patch clamp has been used to quantify the electrical connection between CM and MFB pairs [14,38], but not in a syncytium, which allows for measurement of macroscopic CV, and has different electrophysiology than single cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the promoter they used may not be limited to non-CMs, particularly in areas of injury [48]. Furthermore, non-CMs are better voltage followers than drivers when coupled to CMs because of their higher sarcolemmal resistance and lower sarcolemmal currents, as discussed in [37]. While the lack of an MFBspecific promoter remains a challenge, this study shows that using a similar design with an optogenetic actuator instead of an optogenetic sensor may be better suited to determine whether MFBs are sufficiently connected to CMs to cause conduction slowing and spontaneous beating in vivo under conditions of activated, inward MFB current.…”
Section: Discussionmentioning
confidence: 99%
“…Optogenetics hold great potential in investigating heterocellular coupling between cardiomyocytes and non-cardiomyocytes, both on healthy and infarcted hearts (Yu et al, 2017). Investigators have shown the role of heterocellular coupling between scar tissue (myofibroblasts) and un-injured cardiomyocytes in situ following infarction and such couplings are suspected to induce adverse outcomes, such as arrhythmias (Miragoli et al, 2006;FIGURE 6 | Optogenetic pacing of rat hearts in an open chest (left) and a closed chest (right) configurations (A).…”
Section: Cell-cell Couplingmentioning
confidence: 99%
“…However, some of the potential advantages of using optogenetic proteins (e.g., VSFP2.3), instead of organic dyes for such applications, would be their non-toxicity, noncardiotoxicity, and feasibility of performing repeated in situ observations on target cells for a longer period of time (Chang Liao et al, 2015;Koopman et al, 2017). Enhanced coupling between cardiomyocytes and noncardiomyocytes after myocardial injury is mediated by phenotypic changes in the fibroblasts, which results in an increased connexin expression and also in an emergence of nanotubes-like structures between the cell types (Quinn et al, 2016;Yu et al, 2017). Determination of heterocellular coupling is also useful in assessing the electrophysiological maturity of stem-cell derived cardiomyocytes (e.g., iPSC-CM) following transplantation, since electrical coupling between transplanted cells and native cardiomyocytes may indicate the conductivity and the functionality of the graft in the FIGURE 8 | An automated hybrid bioelectric system for the restoration of sinus rhythm during atrial fibrillation.…”
Section: Cell-cell Couplingmentioning
confidence: 99%
“…Recent applications of this approach include attempts to selectively induce expression of genetically-encoded voltage indicators in cardiac fibroblasts to assess whether the latter cells couple electrically with working myocytes in vivo (14). As explained by Yu et al (15), results from studies involving optogenetic sensor can be challenging to interpret because of issues with promoter promiscuity (e.g., the WT1 promoter used in the latter study has also been shown to drive expression in myocytes (16)). Nonetheless, this methodology has the potential to enable experimental approaches that were once thought impossible.…”
Section: Introductionmentioning
confidence: 99%